2014
DOI: 10.1152/ajpheart.00638.2013
|View full text |Cite
|
Sign up to set email alerts
|

ATP-binding cassette transporter Abcg2 lineage contributes to the cardiac vasculature after oxidative stress

Abstract: CM. ATP-binding cassette transporter Abcg2 lineage contributes to the cardiac vasculature after oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…In contrast to our findings with the cardiac lineage, we did not observe a difference in Abcg2 lineage-labeled endothelial cells when tamoxifen was delivered at different time points. This observation is consistent with prior observations that the Abcg2 lineage contributes significantly to endothelial cells [15].…”
Section: Abcg2 Lineage Labels Cardiomyocytes and Vascular Cells In Thsupporting
confidence: 93%
See 4 more Smart Citations
“…In contrast to our findings with the cardiac lineage, we did not observe a difference in Abcg2 lineage-labeled endothelial cells when tamoxifen was delivered at different time points. This observation is consistent with prior observations that the Abcg2 lineage contributes significantly to endothelial cells [15].…”
Section: Abcg2 Lineage Labels Cardiomyocytes and Vascular Cells In Thsupporting
confidence: 93%
“…There was no difference in survival between treatment and control groups both before and after ligation (data not shown). In our prior study, using the same tamoxifen and PQ delivery strategy, we observed no cardiac damage in the absence of injury [15].…”
Section: Abcg2-labeled Cells Contribute To Endothelial Cells But Not mentioning
confidence: 66%
See 3 more Smart Citations